Another Reason for Using Caffeine in Dermocosmetics: Sunscreen Adjuvant - Rosado, Catarina; Tokunaga, Viviane Kaori; Sauce, Rafael; de Oliveira, Camila Areias; Sarruf, Fernanda Daud; Parise-Filho, Roberto; Maurício, Elisabete; de Almeida, Tânia Santos; Velasco, Maria Valéria Robles; Baby, André Rolim (Frontiers in Physiology, 2019)
The excessive exposure to ultraviolet (UV) radiation is the main cause of skin cancer, the most commonly diagnosed cancer in the world. In this context, the development of innovative and more effective sunscreens, with bioactive compounds like caffeine, displaying antioxidant and anticancer potential, is required. This research work assessed in vitro and in vivo the efficacy and safety of topical sunscreen formulations containing caffeine as an adjuvant of the UV filters. Sunscreens were prepared with 2.5% w/w caffeine or in the absence of this compound. In order to evaluate the safety of these formulations, stratum corneum hydration, skin barrier and colorimetry were assessed in vivo in healthy subjects before and after skin treatment with the samples. The efficacy of the sunscreens was assessed in vitro, using PMMA plates and a spectrophotometer equipped with an integrating sphere; and in vivo by the determination of the sun protection factor (SPF). None of the formulations caused erythema or impaired the skin barrier function. The in vitro functional characterization showed higher SPF values for the caffeine formulation. The in vivo studies also confirmed the higher SPF value of the formulation combining caffeine with the filters, compared to the caffeine-free sample. This improvement contributed to an increase of, approximately, 25% in the in vivo anti-UVB protection. In conclusion, caffeine was well tolerated by the skin and increased the photoprotective activity, being a new alternative adjuvant in sunscreens formulation.